Diesel fuel with ultra-high environmental performance - Степенко, О.О.; Новікова, В.Ф. (Proceedings of National Aviation University (archive), 2009)
This work touches the problem of ecological and operating properties of fuel-oils which are produced on territory of Ukraine. The analysis of technical requirements of all of types of fuel-oil which exist on territory of Ukraine is inprocess conducted, expedience of improvement of ecological description of fuel-oils, comparison of standards, grounded on its on the fuel-oils of Ukraine with the European standard of EN 590.